Kecerdasan Buatan dalam Dunia Pendidikan: Peluang, Tantangan, dan Rekomendasi Penelitian Masa Depan - 'Alam, Ghasa Faraasyatul; Wiyono, Bambang Budi; Burhanuddin, Burhanuddin; Muslihati, Muslihati; Mujaidah, Ani (Program Pascasarjana UNU Surakarta, 2024)
Artificial Intelligence (AI) is revolutionizing various aspects of life, including education. AI in education (AIEd) fosters teachers' understanding of students' learning processes, offers personalized and adaptive learning, and provides instantaneous feedback. It has the potential to improve academic performance and reduce educational disparities. This study aims to engage researchers, policymakers, teachers, students, and engineers in a dialogue about AIEd. It provides an overview of studies on opportunities, challenges, and recommendations for future research, focusing on specific educational outcomes. A comprehensive perspective is needed to understand the function of AIEd. This research utilizes bibliometric analysis and systematic literature review to analyze AIEd, presenting results as a specific bibliometric network using the VOSviewer tool. Research findings that AIEd-based environments are enhancing student learning, but their personalized learning is still in its experimental stage. Challenges include a lack of resources and ethical concerns. AI chatbots and interactive books aid language learning, but they also have advantages and disadvantages. The humanities must balance these advantages and disadvantages.